Pengembangan Perangkat Pembelajaran Matematika dengan Model Learning Cycle-5E untuk Meningkatkan Kemampuan Komunikasi Matematis Siswa Kelas X SMA - Nurfazlin Nova; Irwan; Abdurrahman (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
This research is motivated by the ability of students' mathematical communication skills is not achieved yet maximally. It is known from observation and analysis of the test results of students' mathematical communication skills. There are several factors causing low these capabilities, one of them is the unavailability of teaching materials that optimally facilitates students to grow and develop mathematical communication skills. The purpose of this study was to produce valid mathematical learning tools, practices and effective based on the model-5E learning cycle. This type of research is the development by using models Plomp which consists of three phases, namely the preliminary research, prototyping phase and the assessment phase. In the preliminary phase of research carried out a needs analysis, analysis of learners, curriculum analysis, concept analysis, and analysis of existing teaching materials. In development phase was done designing learning equipment with the learning cycle-5E model, and then conducted a formative evaluation to determine the validity of the three specialist mathematics education, educational technology experts and Indonesian experts. Practicality is known through the implementation of learning outcomes observation sheet, interview and questionnaire responses for students and teachers. The effectiveness of the learning equipment can be obtained from the analysis of the test results of learners’ mathematical communication skill were calculated based on learners’ individual mastery.